Scientific overview of Buchada: trends and impact on academic production - Ribeiro, Neila Lidiany; Paixão, Gean Carlos Targino; de Almeida, Katcilanya Menezes; Andrade, Romário Oliveira de; Lima , Thamirys Lorranne Santos; Cordão, Maiza Araújo; Silva, Josiane Veloso da; Muniz , Ana Jaqueline Cavalcante; Silva, Júlio Cezar Bezerra Vilar da; Negreiros, Natalia Ferreira; Santos, Edilayane da Nóbrega (Food Science and Technology, 2025)
This study analyzed scientific research on buchada, a traditional dish from Northeast Brazil, highlighting its low academic and international representation. A total of 21 documents were identified in the Scopus database between 2004 and 2024, mainly concentrated in federal universities in the Northeast, such as the Universidade Federal da Paraíba and the Universidade Federal Rural de Pernambuco. International collaboration is limited, with only one study conducted in partnership with Spain. Journal analysis revealed that 15 journals have published studies on the topic, with the Revista Brasileira de Zootecnia being the most cited. The presence of Food Science and Technology (Brazil) suggests opportunities for research on food safety and microbiological quality. The five most-cited articles discuss dietary strategies and their effects on the organs and viscera of goats and sheep, while few studies focus on the microbiological quality of buchada. Food safety and technological innovation represent promising areas to enhance the appreciation of this product. This study reinforces the need to expand interdisciplinary research, encourage international collaborations, and develop improvements in buchada preservation. Such initiatives could strengthen its academic and economic significance, fostering greater recognition of this traditional food in Brazil and abroad.